Interannual comparison of meiofauna community structure with focus on nematodes in a seagrass site in Southern Guimaras, Philippines for 2016 and 2017. - Isidro, Jezreel Marie D.
The meiofauna assemblages of calaparan seagrass beds were assessed for interannual comparison, with extensive investigation of the nematode taxonomic composition and distribution. Sampling was done in the month of Spetember for the year 2016 and 2017 using two transect lines laid out parallel to the shore, differing in water depth such that the first transect was along the lowest water mark and the other at 1-meter water depth. Three points along each transect, one five-meter apart from another, were chosen as replicates. The overall mean meiofaunal density was 36.61 ind.cm^(-2) with individuals coming from 16 taxa, dominated by nematodes (68.60%), harpacticoids (19.07%), polycahetes (4.06%), cyclopoid (2.76%) and halacaroids (1.02%). The temporal variation, which was found to be significant using two-way ANOVA (p=0.002 < 0.05), was attributed to the effect of temperature-associated environmental characteristics, sample processing or randomness of the distribution of meiofaunal assemblages in the sampled area which resulted to the drastic decrease of meiofaunal density in 2017. Spatial variation was not relevant between transects and among transect-points in each year (p>0.05), coinciding with an earlier study done in Calaparan seagrass beds. Variation of the overall meiofaunal density was considered to be largely due to the variation of the overall nematode densities because of the dominance of this taxon. Both were found exhibiting the same trend in terms of significance or insignificance of temporal and spatial variation in terms of density. A total of 16 nematode families were identified comprising a mean density of 25.11 ind. cm^(-2), only 10 of which occurred in 2017, dominated by Desmodoridae in both years. The other most abundant families were Linhomoeidae, Microlaimidae, Chromadoridae, Cyatholaimidae and Xyalidae, occurring in both years at varying relative abundances. Trophic analysis and distribution follows the findings of other studies which states that nematodes that were epistrate or epigrowth feeders were more abundant or dominant in coarse sands or sandy sediment.